2023
DOI: 10.1021/acs.macromol.3c00835
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Robust and Healable Bromobutyl Rubber Ionomer via Designing the Resonance Isomerization Effect

Abstract: Integrating mechanical robustness with efficient healability under mild conditions is an inevitable requirement for the commercial development of self-healing ionomers. This work reveals that the resonance isomerization effect can be adopted to construct vigorous ionic networks in ionomers. As a proof of concept, 4-(alkylamino) pyridine (DMAP) and its derivatives are selected to react with bromobutyl rubber (BIIR) to fabricate BIIR ionomers. The ionized DMAP moieties manifest a resonance isomerization effect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The associations of ionic compounds covalently bonded to organic polymers, generally dubbed ionomers, can be tuned via the strength of the dipole moment in ion pairs or the grafting density of the dipoles. Ionomers have been widely studied and commercialized as thermoplastics and thermoplastic elastomers, but less attention has been given to the reinforcement of thermoset elastomers by ionic association and related transition metal–ligand association . The sparsity is at least partly attributable to the difficulty in processing ionically functionalized rubber prior to vulcanization.…”
Section: Introductionmentioning
confidence: 99%
“…The associations of ionic compounds covalently bonded to organic polymers, generally dubbed ionomers, can be tuned via the strength of the dipole moment in ion pairs or the grafting density of the dipoles. Ionomers have been widely studied and commercialized as thermoplastics and thermoplastic elastomers, but less attention has been given to the reinforcement of thermoset elastomers by ionic association and related transition metal–ligand association . The sparsity is at least partly attributable to the difficulty in processing ionically functionalized rubber prior to vulcanization.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38] The ionic groups aggregated to form strong physical cross-linkers in the polymer matrix, which promoted the elastic behaviour of the material, improving its strength, toughness, and wear resistance. [39][40][41][42][43][44][45][46][47] Valentin et al reported an ionic elastomer, which exhibited a tensile strength of 40 MPa and an elastic recovery of approximately 90%. 48 Nie et al designed a dynamic dual-cross-linked network strategy for fabricating an ionic elastomer, which showed excellent mechanical properties with a high toughness (33.8 MJ m −3 ) and favorable elasticity (>85%).…”
Section: Introductionmentioning
confidence: 99%